2022
DOI: 10.1002/adma.202203335
|View full text |Cite
|
Sign up to set email alerts
|

Anhydrous Fast Proton Transport Boosted by the Hydrogen Bond Network in a Dense Oxide‐Ion Array of α‐MoO3

Abstract: Developing high‐power battery chemistry is an urgent task to buffer fluctuating renewable energies and achieve a sustainable and flexible power supply. Owing to the small size of the proton and its ultrahigh mobility in water via the Grotthuss mechanism, aqueous proton batteries are an attractive candidate for high‐power energy storage devices. Grotthuss proton transfer is ultrafast owing to the hydrogen‐bonded networks of water molecules. In this work, similar continuous hydrogen bond networks in a dense oxid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 62 publications
(114 reference statements)
2
26
0
1
Order By: Relevance
“…The remaining 1.0 H + can be extracted when applying a constant voltage at the end of deprotonation for 3 h (Figure S4, Supporting Information). The CV curves share large resemblances with that in a 32 mol kg −1 (m) ZnCl 2 + 1 m P 2 O 5 electrolyte in our previous study, [23] indicating the same H + intercalation mechanism in α-MoO 3 . More specifically, we ascribed the corresponding peaks observed for H x MoO 3 (1< x <2.5) in the subsequent cycles to the redox events of proton (de)intercalation, H 1 MoO 3 /H x MoO 3 and H x MoO 3 /H 2.5 MoO 3 (0< x <1.5); equations 1, 2, 3, and 4 are used to interpret the cathodic peaks (C1 and C2) and anodic peaks (A3 and A4), respectively, in agreement with previous electrochemical studies.…”
Section: Fast Deprotonation Of Moo 3 Enabled By Facile Anhydrous Prot...supporting
confidence: 76%
See 2 more Smart Citations
“…The remaining 1.0 H + can be extracted when applying a constant voltage at the end of deprotonation for 3 h (Figure S4, Supporting Information). The CV curves share large resemblances with that in a 32 mol kg −1 (m) ZnCl 2 + 1 m P 2 O 5 electrolyte in our previous study, [23] indicating the same H + intercalation mechanism in α-MoO 3 . More specifically, we ascribed the corresponding peaks observed for H x MoO 3 (1< x <2.5) in the subsequent cycles to the redox events of proton (de)intercalation, H 1 MoO 3 /H x MoO 3 and H x MoO 3 /H 2.5 MoO 3 (0< x <1.5); equations 1, 2, 3, and 4 are used to interpret the cathodic peaks (C1 and C2) and anodic peaks (A3 and A4), respectively, in agreement with previous electrochemical studies.…”
Section: Fast Deprotonation Of Moo 3 Enabled By Facile Anhydrous Prot...supporting
confidence: 76%
“…The unique proton transfer based on hydrogen bond networks in solid structures for fast proton transport in α‐MoO 3 and CuFe‐TBA could rationalize the persisting hydrogen generation under high current densities. Indeed, the proton diffusion barriers in α‐MoO 3 and CuFe‐TBA are < 0.3 eV, [ 19,23 ] resembling that in liquid water via the Grotthuss mechanism (< 0.4 eV), thanks to the dense oxide ion arrays (O‐O distance < 3 Å) in α‐MoO 3 and abundant structural water in CuFe‐TBA that facilitate the proton hopping. In contrast, Ni(OH) 2 , with O‐O distance of ≈3.18 Å, exhibit a much larger proton diffusion barrier of > 0.6 eV, [ 39 ] since the proton hopping barrier is positively related to the O‐O distance as evidenced by density functional theory (DFT) calculations (Figure S20, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, Ma et al [77] revealed the fast proton transport mechanism of the MoO 3 cathode through experiments and theoretical calculations. Similar to the Grotthuss proton transport mechanism of water molecules, protons form a hydrogen bond network in the α-MoO 3 cathode lattice of the ultra-concentrated double-ion electrolyte (32 mol kg À 1 ZnCl 2 and 1 mol kg À 1 P 2 O 5 /H 2 O).…”
Section: Aqueous Hydrogen-ion Batteriesmentioning
confidence: 99%
“…In recent studies, Ma et al [77] . revealed the fast proton transport mechanism of the MoO 3 cathode through experiments and theoretical calculations.…”
Section: Electrochemical Energy Storage Application Of Molybdenum Tri...mentioning
confidence: 99%